Flood Disaster Risk Reduction and Adaptation Around the Coastal Area of Bangladesh (Journal of Environmental Science and Natural Resources, 2015)
This study was undertaken to investigate the strategies for flood disaster risk reduction and adaptation around the coastal area of Bangladesh. Education level and environmental awareness, family size, farm size, adaptation tools, loss due to flood disaster, adaptation tools and area of the rivers and canals of the localities were taken as independent variables. On the other hand, pre and post flood activities were considered as dependent variable of the study. Pre flood activities such as miking around the flood disaster areas reduced flood risk 44.2%, radio and TV bulletin 25.0%, enclosure tube-well by polythene bag 16.7% and shifting the people to cyclone center reduced flood risk 14.2%. However, post flood activities such as food and water supply contributed 48.3% and activities of medical rescue team (i.e. provide medicine, vaccination and saline) and agricultural inputs supply (i.e. seed, fertilizer, livestocks, fisheries) contributed the same percentage i.e. 25.8% to adapt flood disaster. These variables were tested to explore the relationship between the dependent and independent variables. Education level and environmental awareness, family size, farm size, adaptation tools, loss due to flood disaster were significantly correlated with the pre and post flood activities for flood disaster risk reduction and adaptation around the coastal areas. The findings indicated that the lower the education level and environmental awareness of the coastal area people the lower is the activities (pre and post) during flood disaster in flood disaster risk reduction and adaptation. The findings also indicated that the pre flood preparation is not enough for flood disaster risk reduction and adaptation around the coastal area of Bangladesh and adaptation tools were not sufficient for flood disaster risk reduction and adaptation around the coastal area s of Bangladesh.DOI: http://dx.doi.org/10.3329/jesnr.v6i1.22040 J. Environ. Sci. & Natural Resources, 6(1): 53-57 2013